The Role of CRISPR-Cas9 in Gene Editing - Mohammed J. Kadhim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The CRISPR-Cas9 technique is a contemporary technology that has transformed the process of genetic modification, allowing scientists to target genomes in living organisms with precision and simplicity. Numerous practical applications of significant importance, including the introduction of new genes into living cells, are facilitated by the CRISPR-Cas9 system's advanced level of gene targeting, precision, and simplicity of use. An enigmatic process involving repeated DNA sequences in E. coli initiated the emergence of this CRISPR-Cas9 mechanism. After observing this phenomenon in bacteria, scientists initiated an investigation into its function. It was noted that E. coli employs it as a self-defence mechanism against bacteriophage attacks and plasmids. CRISPR-Cas9, a novel method for genetic modification, was created as a result of this investigation. This system has been re-engineered by scientists to be more broadly applicable, allowing for the modification of the genetic code of virtually any organism, surpassing the scope of self-defence. The CRISPR-Cas9 system-based gene editing mechanisms have the potential to produce substantial results that were previously difficult to achieve. Nevertheless, the question of genetic modification through the application of this technology prompts debates and demands for the resolution of the ethical, social, and legal issues that are associated with its application. The potential applications of the CRISPR-Cas9 system are seemingly boundless.